Insecticide-contaminated honeydew: risks for beneficial insects - Calvo-Agudo, Miguel; Tooker, John F.; Dicke, Marcel; Tena, Alejandro (Wiley Online Library, 2021)
Honeydew is the sugar-rich excretion of phloem-feeding hemipteran insects such as aphids, mealybugs, whiteflies, and psyllids, and can be a main carbohydrate source for beneficial insects in some ecosystems. Recent research has revealed that water-soluble, systemic insecticides contaminate honeydew excreted by hemipterans that feed on plants treated with these insecticides. This contaminated honeydew can be toxic to beneficial insects, such as pollinators, parasitic wasps and generalist predators that feed on it. This route of exposure has now been demonstrated in three plant species, for five systemic insecticides and four hemipteran species; therefore, we expect this route to be widely available in some ecosystems. In this perspective paper, we highlight the importance of this route of exposure by exploring: (I) potential pathways through which honeydew might be contaminated with insecticides; (II) hemipteran families that are more likely to excrete contaminated honeydew; and (III) systemic insecticides with different modes of action that might contaminate honeydew through the plant. Furthermore, we analyse several model scenarios in Europe and/or the USA where contaminated honeydew could be problematic for beneficial organisms that feed on this ubiquitous carbohydrate source. Finally, we explain why this route of exposure might be important when exotic, invasive, honeydew-producing species are treated with systemic insecticides. Overall, this review opens a new area of research in the field of ecotoxicology to understand how insecticides can reach non-target beneficial insects. In addition, we aim to shed light on potential undescribed causes of insect declines in ecosystems where honeydew is an important carbohydrate source for insects, and advocate for this route of exposure to be included in future environmental risk assessments.